ТАЄМНІ ДОКУМЕНТИ ЗАПОРІЗЬКОГО ОБКОМУ КП УКРАЇНИ ПРО ПОЛІТИЧНУ БОРОТЬБУ В РЕГІОНІ НАПЕРЕДОДНІ ПРОГОЛОШЕННЯ НЕЗАЛЕЖНОСТІ 1991 Р. (Zaporizhzhia Historical Review, 2021)
The publication introduces into scientific appeal the part from unique after it informative potential selection of documents about socio-political situation in Zaporizhzhya region and activity of opposition forces on the eve of the receipt of independence by Ukraine in 1991. As especially secret and such, that too brightly illustrated the methods of communist party work, these documents after prohibition of activity of KPRS were made an attempt to be destroyed by the workers of party organization in August in 1991. But they succeeded to be saved, and today they are saved in private collection.